White matter lesion location correlates with disability in relapsing multiple sclerosis. Issue 1 (February 2020) - Gaetano, Laura; Magnusson, Baldur; Kindalova, Petya; Tomic, Davorka; Silva, Diego; Altermatt, Anna; Magon, Stefano; Müller-Lenke, Nicole; Radue, Ernst-Wilhelm; Leppert, David; Kappos, Ludwig; Wuerfel, Jens; et al.
Background: Lesion location is a prognostic factor of disease progression and disability accrual. Objective: To investigate lesion formation in 11 brain regions, assess correlation between lesion location and physical and cognitive disability measures and investigate treatment effects by region. Methods: In 2355 relapsing–remitting multiple sclerosis patients from the FREEDOMS and FREEDOMS II studies, we extracted T2-weighted lesion number, volume and density for each brain region; we investigated the (Spearman) correlation in lesion formation between brain regions, studied association between location and disability (at baseline and change over 2 years) using linear/logistic regression and assessed the regional effects of fingolimod versus placebo in negative binomial models. Results: At baseline, the majority of lesions were found in the supratentorial brain. New and enlarging lesions over 24 months developed mainly in the frontal and sublobar regions and were substantially correlated to pre-existing lesions at baseline in the supratentorial brain ( p = 0.37–0.52), less so infratentorially ( p = −0.04–0.23). High sublobar lesion density was consistently and significantly associated with most disability measures at baseline and worsening of physical disability over 24 months. The treatment effect of fingolimod 0.5 mg was consistent across the investigated areas and tracts. Conclusion: These results highlight the role of sublobar lesions for the accrual of disability in relapsing–remitting multiple sclerosis.